Exosomes as smart drug delivery vehicles for cancer immunotherapy - Zhang, Huan; Wang, Simiao; Sun, Man; Cui, Yaxin; Xing, Jianming; Teng, Lesheng; Xi, Zhifang; Yang, Zhaogang (Frontiers in Immunology, 2023)
Exosomes (Exos) as drug delivery vehicles have been widely used for cancer immunotherapy owing to their good biocompatibility, low toxicity, and low immunogenicity. Some Exos-based cancer immunotherapy strategies such as tuning of immunosuppressive tumor microenvironment, immune checkpoint blockades, and cancer vaccines have also been investigated in recent years, which all showed excellent therapeutic effects for malignant tumor. Furthermore, some Exos-based drug delivery systems (DDSs) for cancer immunotherapy have also undergone clinic trails, indicating that Exos are a promising drug delivery carrier. In this review, in order to promote the development of Exos-based DDSs in cancer immunotherapy, the biogenesis and composition of Exos, and Exos as drug delivery vehicles for cancer immunotherapy are summarized. Meanwhile, their clinical translation and challenges are also discussed. We hope this review will provide a good guidance for Exos as drug delivery vehicles for cancer immunotherapy.